Deformation behavior and microstructural evolution of hydrogenated Ti44Al6Nb alloy during thermo-compression at 1373–1523 K. (15th October 2016) - Chen, Ruirun; Ma, Tengfei; Guo, Jingjie; Ding, Hongsheng; Su, Yanqing; Fu, Hengzhi
Abstract: The effect of hydrogen on the hot deformation behaviors of Ti44Al6Nb alloy is investigated at temperature range from 1373 K to 1523 K and the strain rate range from 0.001 s − 1 to 1 s − 1 on Gleeble-1500D thermo-simulation machine. Experimental results show that the peak stress shows a decreasing trend with increasing hydrogen content, which indicates that hydrogen promotes a solid solution softening effect additional to that produced by dynamic recrystallization (DRX) and hydrogen-induced dislocation movement, the fraction of DRX increases with the increase of hydrogen content, while the fraction of LABs and the dislocation density decrease with the increase of hydrogen content. Similarly, the deformation activation energy of hydrogenated titanium aluminides is calculated to be 382.9 kJ/mol compared with that of 485.7 kJ/mol for unhydrogenated alloy indicating that hydrogen promotes the onset of DRX. The hot processing window is constructed based on the dynamic material model (DMM), which is broadened by hydrogen suggesting that hydrogen contributes to the hot workability of high Nb contained titanium aluminides. Graphic abstract: Highlights: Hydrogen can decrease the flow stress of Ti44Al6Nb alloy by 40%. Hydrogen decreases the deformation activation energy. Hydrogen promotes the dynamic recrystallization and dislocation movement. Hydrogen broadens the window of hot processing of TiAl alloys